Microvesicles: What is the Role in Multiple Sclerosis? - Carandini, Tiziana; Colombo, Federico; Finardi, Annamaria; Casella, Giacomo; Garzetti, Livia; Verderio, Claudia; Furlan, Roberto (Frontiers in Neurology, 2015)
Microvesicles are a recently described way of cell communication that has been implicated in a number of biological processes, including neuroinflammation. Widely investigated as biomarkers in oncology and neurological disorders, little is known of the role of microvesicles in the pathogenesis of diseases such as multiple sclerosis. Several evidences suggest that pro-inflammatory microglia and infiltrating macrophages release microvesicles that spread inflammatory signals and alter neuronal functions. We review here available information on microvesicles, with a special focus on microglia and macrophage microvesicles, in the pathogenesis of multiple sclerosis, and as potential biomarkers and therapeutic targets.